Correction: Polypyrrole multilayer-laminated cellulose for large-scale repeatable mercury ion removal. Issue 39 (26th September 2018) - Hanif, Zahid; Lee, Seyeong; Qasim, Ghulam Hussain; Ardiningsih, Indah; Kim, Jeong-Ah; Seon, Jaeyoung; Han, Seunghee; Hong, Sukwon; Yoon, Myung-Han
Abstract : Correction for 'Polypyrrole multilayer-laminated cellulose for large-scale repeatable mercury ion removal' by Zahid Hanif et al., J. Mater. Chem. A, 2016, 4, 12425–12433.